Analisis Kualitas Fisika Tanah Areal Perkebunan Kelapa Sawit pada Umur Tanaman yang Berbeda di Desa Tetewatu Kecamatan Wiwirano Kabupaten Konawe Utara - Ma’ruf, Amal; Darwis, Darwis; Leomo, Leomo; Alam, Syamsu; Pasolon, Yulius B; Rustam, La Ode (CV. Eduartpia Publisher, 2023)
The research aims to determine the physical quality of soil in oil palm plantation areas at different ages in Tetewatu Village and the direction of soil physical quality management to increase the productivity of oil palm plantations in Tetewatu Village. The research was conducted in Tetewatu Village, Wiwirano Sub-district from October 2022 to January 2023. The research method used a survey method based on the age of oil palm. Determination of sampling is done by adjusting the age of the plant with the conditions in the field, determining the sample point at each age of oil palm plants (5 years, 10 years and 15 years). Whole soil samples were taken using ring samples at a depth of 0-30 cm and 30-60 cm and then analyzed in the laboratory. The data obtained were analyzed using variance analysis (Anova) and differences in treatment means were tested using the BNJ test. The results showed that different plant ages affected the content weight at a depth of 0-30 cm and porosity at a depth of 0-30 cm (real). But no significant effect on soil moisture content (KAT). And the direction of soil management that needs to be recommended to improve soil quality in oil palm plants in Tetewatu Village, Wiwirano District, North Konawe Regency is to provide good nutrients for oil palm plants, one of which is through the application of organic materials.Keywords : analysis of variance, soil quality, soil physical properties